Phenolics and antioxidant activity of aqueous turmeric extracts as affected by heating temperature and time. (May 2019) - Park, Chang Yang; Lee, Kyo-Yeon; Gul, Khalid; Rahman, M. Shafiur; Kim, Ah-Na; Chun, Jiyeon; Kim, Hyun-Jin; Choi, Sung-Gil
Abstract: The extraction efficiency of bioactive compounds along with their biological activity and stability depends on the extraction temperature and time. The effects of extraction temperature (60–90 °C) and time (15–180 min) on the total soluble solids (TSS) content, antioxidant activity, and curcuminoids of aqueous turmeric extracts were studied. The stability of extracts based on curcuminoid degradation, loss of antioxidant activity and color was also investigated by further heat treatment at 90 °C and 25 °C for 48 h. The TSS showed temperature dependency, reached a maximum value within 60 min and then plateaued for all temperatures. The maximum TSS and curcuminoid concentration were obtained at an extraction temperature and time of 90 °C and 60 min, respectively. Antioxidant activity increased with both increasing temperature and time. After infusing the extracts at 90 °C for 1 h followed by separation, further heat treatment at 90 °C for 48 h resulted in curcuminoid degradation and reduced antioxidant activity while no changes were observed in extracts kept at 25 °C for the same time. High extraction temperature for appropriate time results in high TSS and high antioxidant activity. However, excessive heat treatment led to the degradation of curcuminoids and reductions in antioxidant activity. Highlights: Aqueous extraction of turmeric as a function of temperature and time is reported. Effects on TSS content, antioxidant activity, and curcuminoids were studied. The stability of extracts was investigated by further heating at 90 °C and 25 °C for 48 h. The ideal extraction condition in this study was 90 °C for 60 min. Further heat treatment at 90 °C for 48 h resulted in curcuminoid degradation.